Pengaruh Kualitas Aplikasi, Service Convenience, Dan Fenomena Panic Buying Saat Pandemi Covid-19 Terhadap Intensitas Pembelian Pada Market Place Tokopedia - Vebrico Windy Satriya (PRAGMATIS, 2021)
The primary aim of this research is to identify the effect of quality application, service convenience, and panic buying phenomena during the covid-19 pandemic towards buyers' purchase intensity on marketplace namely Tokopedia. By using a non probability sampling technique, a sample of 90 respondent is obtained and the number is considered properly represent the total population of Tokopedia's consumers especially around RW 03 Sedayu, Surabaya. The analysis of data used is multiple linear regression analysis. The result of the study indicates that a quality of one application has a significant influence on purchase insensity and thus becomes the dominant variable factor. Meanwhile, service convenience does not hold crucial parts on the purchasing intensity. The Adjusted R Square coefficient of 47.8% of the unit describes that the variant shifts of value in purchase intensity can explain its direct effect through application quality value changing variation, service convenience, and panic buying by 47.8% in unit.